COVID-19 Spread and Financial Distress: Does Managerial Ability Matter? - Kushermanto, Andi; Alisa, Inayah Risqi; Ulum, Akhmad Samsul; Zulaikha, . (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The COVID-19 pandemic has caused a global-scale economic crisis. This study aims to examine the impact of the COVID-19 spread on financial distress and the moderating role of managerial ability in the relationship between the COVID-19 spread and financial distress. The population of this study is manufacturing companies listed on the Indonesian Stock Exchange between 2017 and 2021. Using purposive sampling techniques, 31 companies were selected as the samples (155 firm-year observations). Data were collected from the companies financial statements and were analyzed using Partial Least Squares (PLS)-Structural Equation Modeling (SEM). The results of this study indicate that the COVID-19 spread has a positive effect on financial distress. Furthermore, managerial ability is a moderating factor that weakens the influence of the COVID-19 spread on financial distress. This study provides evidence that managerial ability is an important factor in managing company resources and is related to the company's efforts in dealing with the crisis caused by the COVID-19 spread.